Pembuatan Busana Fantasi Aplikasi Bunga Tulip, Kupu-Kupu, Hiasan Kepala Elang Falcon - Rosita Novarida; Edi Suwasana (Garina, 2025)
Fantasy Party Dress is a dress shows beauty and uniqueness. This cloth is that worn for certain events, based on the occasion, fantasy clothing is only used in fashion gshows/carnivals. The purpose of making a report is to find out the process of making a fantasy party dress for the application of tulips, butterflies and falcon headdresses. The report uses qualitative research methods, literature, observation, documentation and data analysis. The making of this Fantasy Party Dress goes through the stages, 1) determining the design, 2) Making an S size pattern, 3) Cutting the main material, furing, lining material, 4) Pressing the coating on the main material, 5) Merader, 6) Sewing the material, sewing the rufle skirt then sewing on skirt, 7) Installation of the application of butterfly embroidery with the check technique, 8)Determining the falcon headdress and determining the appropriate color, 9)The process of sewing parel with the jidot technique, 10)Finishing it by examining the details of the dress. The process of making fantasy clothes is carried out carefully and carefully, to produce clothes that match the design and size. Sew the camisol loop by exaggerating the thread at the end of the stitch, the end of the thread is inserted into the eye of the hand needle, the needle is inserted into the loop, pulled upside down. Sequins using the jidot technique (parallel sequins with one key at a time)